Future priorities in tackling infections due to brain-eating amoebae - Khan, Naveed Ahmed *; Anwar, Ayaz *; Siddiqui, Ruqaiyyah Bano * (American Chemical Society, 2017)
Brain-eating amoebae (Acanthamoeba spp., Balamuthia mandrillaris and Naegleria fowleri) can cause opportunistic infections involving the central nervous system. It is troubling that the mortality rate is more than 90% despite advances in antimicrobial chemotherapy over the last few decades. Here, we describe urgent key priorities for improving outcomes from infections due to brain-eating amoebae.